Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5713/ajas.2011.11132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Keratinase on Performance, Nutrient Utilization, Intestinal Morphology, Intestinal Ecology and Inflammatory Response of Weaned Piglets Fed Diets with Different Levels of Crude Protein

Abstract: Two experiments were conducted to investigate the in vitro ability of keratinase to hydrolyze soybean glycinin and β-conglycinin and to evaluate the in vivo effects of keratinase when included in corn-soybean diets with different levels of crude protein and fed to nursery pigs. In experiment 1, a saturated keratinase solution (1 ml) was added to two blank controls of either glycinin or β-conglycinin resulting in the hydrolysis of 94.74% glycinin and 88.89% β-conglycinin. In experiment 2, 190 pigs (8.3±0.63 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 38 publications
(59 reference statements)
7
46
1
1
Order By: Relevance
“…1 was 306 and 612 U/g respectively, for the diets supplemented with 0.05 or 0.1% keratinase, and calculated keratinase activity in keratinase supplemental diets for Exp. Recent in vitro work conducted in our laboratory demonstrated that keratinase hydrolysed both soybean glycinin and b-conglycinin (Wang et al 2011), which reinforced the explanation proposed by Tu et al (1998). The hydrolysing ability of keratinase on various proteins of animal or plant origin has been widely shown in vitro (Yu et al 1972;Lin et al 1996;Gradisˇar et al 2005).…”
Section: Discussionsupporting
confidence: 86%
“…1 was 306 and 612 U/g respectively, for the diets supplemented with 0.05 or 0.1% keratinase, and calculated keratinase activity in keratinase supplemental diets for Exp. Recent in vitro work conducted in our laboratory demonstrated that keratinase hydrolysed both soybean glycinin and b-conglycinin (Wang et al 2011), which reinforced the explanation proposed by Tu et al (1998). The hydrolysing ability of keratinase on various proteins of animal or plant origin has been widely shown in vitro (Yu et al 1972;Lin et al 1996;Gradisˇar et al 2005).…”
Section: Discussionsupporting
confidence: 86%
“…It has been proved that treatment of SBM with appropriate proteases may improve piglet performance at weaning, which would be a potential method for increasing the amounts of SBM in starter diets for weaned piglets (Rooke et al, 1998). Protease had a positive effect on the ATTD of DM, GE, and CP in weaned piglets (Wang et al, 2011a). However, there are still some insignificant proteases in diets (Ji et al, 2008; Adeola and Cowieson, 2011; O’Shea et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the proteins in SBM are easily digested, but some proteins including glycinin, protease inhibitor and antigenic proteins are difficult to digest, especially for newly weaned pigs, which may damage intestinal health and impair immune function (Brandon and Friedman, 2002; Sun et al, 2008; Zhao et al, 2008; Wang et al, 2011a;b). Fortunately, with the developing of feed enzyme technologies, protease treatment of SBM is an alternative means to reduce the antigenic challenge of SBM and improve performance of animals (Rooke et al, 1998; Piao et al, 1999; Yu et al, 2007; Romero et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…studies reported an increase in weight gain and reduced feed conversion with protease supplementation in crude protein and amino acid reduced diets [8,9]. In contrast, another study mentioned the inconsistency in body weight gain and feed intake when proteases supplemented with crude protein and amino acid reduced diets [10].…”
Section: Fig 1 Body Weight Gain (G) and Fcr Of Broilers Fed With CC mentioning
confidence: 99%